Decarboxylation of glycine on icy grain surfaces: a first-principle investigation. Issue 4 (14th October 2022) - Xavier, Neubi F; da Silva, Antonio M; Sacchi, Marco; Bauerfeldt, Glauco F
ABSTRACT: Much effort has been devoted to the investigation of the reactivity of glycine, the smallest amino acid, in different environments in the interstellar medium (ISM). While the formation paths are expected to follow a gas-solid mechanism, the full picture of glycine survival in the ISM remains yet unrevealed. In this work, we have adopted density functional theory under periodic boundary conditions to simulate mechanisms for the decarboxylation of glycine on a water-rich surface and on a glycine ice. We have performed calculations at the PBE-D3/USPP level, from which several adsorption modes of glycine on each surface were investigated and decomposition mechanisms into CO2 and CH3 NH2 on the different interfaces were suggested. Most favourable adsorption sites of glycine have adsorption energies of −106.54 and −98.52 kJ mol −1 on the water ice and glycine ice, respectively. Glycine decomposes into CO2 and CH3 NH2 through a two-step mechanism on the water ice and four-step mechanism on the glycine surface, from which the barrier heights of the determinant steps were of 288.98 and 111.58 kJ mol −1, respectively. At temperatures of 50 K, decomposition of glycine into CO2 and CH3 NH2 is an exergonic reaction, pointing to a thermodynamically controlled reaction in specific interstellar regions, such as hot-cores. Compared with reported glycine gas-phase reaction, much lower barrier heights for glycine formation were found in the surface models studied here.